Two-thirds of older people is interested in information meetings on end-of life care to stimulate advance care planning: a national survey - Tessa D. Bergman; Annicka G. M. van der Plas; Bregje D. Onwuteaka-Philipsen; H. Roeline W. Pasman (BMC Geriatrics)
Abstract Background Information meetings are a way to create awareness and inform older people on end-of-life care and have shown to stimulate advance care planning (ACP). Before further development and implementation, it is important to explore older people’s preferences regarding these meetings. This study aims to explore which older people are interested, whether this is associated with previous ACP behaviour, and their preferences regarding the content and organisation of information meetings. Methods A cross-sectional study was conducted on a randomly drawn sample of 1242 Dutch older people (≥ 65 years; response 93.2%) from a nationwide panel. In September 2020, they received a questionnaire on palliative care, including questions on interest in attending an information meeting. Descriptive statistics, chi-square tests, and regression analyses were performed. Results One-third of respondents reported they would attend an information meeting if they were invited this week (33.5%), 33.2% (possibly) in the future and 33.3% would not attend. Respondents who had thought about end-of-life topics (OR 2.54 CI 1.63–3.96) were more likely to be currently and (possibly) interested in the future in attending an information meeting compared to those who had not. Main topics of interest included possibilities for care at home (88.1%), symptom relief (87.7%), and advance directives (80.6%). Further, respondents preferred to be invited through a personal invitation from their general practitioner (51.2%) or another organisation such as the municipality (54.7%). Also, they preferred their own general practitioner (48.3%) or another healthcare facility such as a hospital or care home (17.9%) to organise information meetings. Conclusions This study shows that information meetings on end-of-life care are appealing to a large and diverse group of older people. Information meetings should cover a broad range of topics, ranging from possibilities of care at home and symptom relief to end-of-life decisions. For these meetings, older people prefer to be invited through a personal letter and value the involvement of their general practitioner. Therefore, meetings should preferably be organised by or in collaboration with the general practitioner.